Answer:
C=7
Step-by-step explanation:
Because it's a right angle in total we know the 2 expressions combined will equal 90.
(8c-5)+(6c-3)=90
-2x-2 is your equation :) <span />
The missing justification in the proof is
<span>B) Substitution property of equality
The expression for sin</span>² x and cos² x is substituted to the other side of the equation. Since sin x = a/c, then sin² x = a²/c². Similarly, since cos x = b/c, then cos² x = b²/c². Adding to two results to the third statement.
multiply -2/25 x 5 hours
-2/25 x 5/1 = -10/25 = -2/5
Answer:
x = 75
Step-by-step explanation:
Triangle BDH
The angle must add to 180 degrees
36+ 39 + DHB = 180
75 + DHB = 180
DBH = 180-75
DHB = 105
DBH + x = 180 since it is a straight line
105+ x = 180
x = 75